Gambaran Kualitas Hidup Orang dengan HIV/AIDS (ODHA) - Liyanovitasari Liyanovitasari (Program Studi S1 Keperawatan Universitas Ngudi Waluyo, 2020)
According to WHO data in 2017, 36.9 million people were living with HIV and 59% were receiving antiretroviral treatment. HIV / AIDS is an infectious disease caused by infection with the Human Immunodeficiency Virus. HIV / AIDS creates a variety of very complex problems so that HIV patients is required to be able to face problems that impact on their quality of life. The purpose of this study was to describe the quality of life of HIV patients. This type of research is analytical survey research. The approach used is a descriptive approach. The population in this study were all people with HIV / AIDS who were gathered in the Holy Love Peer Support Group, Central Java with a total of 129 members. Sample of 57 people with purposive sampling technique. The instrument used was the WHOQOL-BREF questionnaire for quality of life. Univariate analysis using frequency distribution and percentage. The results showed that most of the respondents had a moderate quality of life, namely as many as 39 respondents (68.4%). This research is expected that HIV patients will be able to recognize and develop their abilities so that they can improve the quality of life of HIV patients.Key words:Quality of lifeHIV/AIDS patients